Effect of Nb content on the properties of Al0.1CoCrFeNi high-entropy alloy - Mingchun Zhao; Lin Huang; Ke Zhang; Ke Xiong; Dashan Guo; Wei Feng (Journal of Materials Research and Technology, 2025)
A series of Al0.1CoCrFeNi-xNb (x = 0, 1, 3, 5, 7, 9 wt%) high-entropy alloys (HEAs) were prepared using high-energy ball milling and Spark Plasma Sintering (SPS) methods. The influence of Nb element doping on the microstructure and properties of Al0.1CoCrFeNi HEAs was systematically studied through tensile testing, hardness testing, friction and wear testing, and microstructure observation. The results showed that with the increase of Nb content, the phase structure of Al0.1CoCrFeNi-xNb high-entropy alloys (subsequently represented by Al0.1-xNb HEAs changed, transforming the alloy structure from a single FCC to a dual-phase structure of FCC and HCP (Laves phase) mixture. Its tensile strength increased with the increase of Nb content, while its plasticity showed a decreasing trend. As the Nb content increases, the hardness of the alloy significantly increases, from 174.2HV in 0Nb alloy to 384.7HV in 9Nb alloy. Through the analysis of the tensile fracture morphology, it is found that the fracture mainly occurs at brittle intermetallic compounds. For Al0.1-xNb HEAs, when x > 3, the alloy exhibits a quasi-cleavage fracture mechanism, while when x ≤ 3, the alloy exhibits a plastic fracture mechanism. With the increase of Nb content, the average friction coefficient of the alloy shows a trend of first increasing and then decreasing. The wear rate of the alloy gradually decreases from 4.04 × 10−4 mm3/(N · m) of 0Nb to 2.03 × 10−4 mm3/(N · m) of 9Nb, indicating that the wear resistance of the alloy increases. Analysis shows that the wear mechanism of Al0.1-xNb HEAs is abrasive wear, adhesive wear, and slight oxidative wear.